2016
DOI: 10.1177/1053451216630291
|View full text |Cite
|
Sign up to set email alerts
|

Improving Transition Support for Juvenile Offenders With Disabilities Through a Collaborative Approach

Abstract: Collaboration between special educators and transition coordinators is important to lower recidivism rates among juvenile offenders with disabilities. This column provides best practice transition guidelines and urges special education teachers, special education coordinators, and transition coordinators in juvenile correctional facilities to communicate among themselves and other professionals to collaborate during the transition period from the community to confinement and when juveniles with disabilities re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 13 publications
0
38
0
Order By: Relevance
“…Long-term juvenile facilities are for youth who have had their cases adjudicated and will remain there for an extended period of time and can go by various names (e.g., juvenile justice, juvenile care, juvenile corrections), depending on the state (Koyama, 2012). Youth in long-term facilities typically do not receive a specific time sentence like adults; instead, they are required to complete a series of programs to earn their release (Ochoa, 2016).…”
Section: Alternative Education Definedmentioning
confidence: 99%
“…Long-term juvenile facilities are for youth who have had their cases adjudicated and will remain there for an extended period of time and can go by various names (e.g., juvenile justice, juvenile care, juvenile corrections), depending on the state (Koyama, 2012). Youth in long-term facilities typically do not receive a specific time sentence like adults; instead, they are required to complete a series of programs to earn their release (Ochoa, 2016).…”
Section: Alternative Education Definedmentioning
confidence: 99%
“…In order to provide effective transition supports and services to incarcerated youth that build on the strengths of existing transition planning processes, it is crucial that a clear understanding of the existing processes is established. Some studies exist that describe the transition process for incarcerated youth in the United States (see Hirschfield, 2014; Mathur & Griller Clark, 2013; Ochoa, 2016; Risler & O'Rourke, 2009). A thorough search of the literature revealed that few studies exist that discuss the transition back to community that incarcerated youth in Australia experience (see Dawes, 2011; Halsey, 2007; Jarvis, Beale, & Martin, 2000), and none that specifically examined actual transition processes in Australia.…”
Section: The Present Studymentioning
confidence: 99%
“…To support students for whom a transition back to the traditional school is a goal, programming within the AE setting focuses on that transition, beginning when a student enters the AE setting (Johnson et al, 2017; Jolivette et al, 2012; Ochoa, 2016). Elements of such programming include (a) maintenance of any existing individualized education program (IEP), (b) an academic curriculum aligned with that used in the traditional school, (c) access to all related services (e.g., mental health provider, speech-language pathologist), (d) collaboration among all service providers, (e) adherence to all state and local testing requirements, and (f) a clear action plan (Atkins & Bartuska, 2010).…”
mentioning
confidence: 99%